2004
DOI: 10.3732/ajb.91.6.966
|View full text |Cite
|
Sign up to set email alerts
|

A chemotaxonomic analysis of cannabinoid variation in Cannabis (Cannabaceae)

Abstract: Cannabinoids are important chemotaxonomic markers unique to Cannabis. Previous studies show that a plant's dry-weight ratio of Δ(9)-tetrahydrocannabinol (THC) to cannabidiol (CBD) can be assigned to one of three chemotypes and that alleles B(D) and B(T) encode alloenzymes that catalyze the conversion of cannabigerol to CBD and THC, respectively. In the present study, the frequencies of B(D) and B(T) in sample populations of 157 Cannabis accessions were determined from CBD and THC banding patterns, visualized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
286
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(305 citation statements)
references
References 49 publications
11
286
0
1
Order By: Relevance
“…4). GC analysis of chemotype II has typically demonstrated a more narrow range skewed towards a high CBD total to THC total ratio (De Meijer et al 1992;Hillig and Mahlberg 2004;Weiblen et al 2015), although a low CBD total to THC total ratio similar to those reported here have been observed in Southeast Asian landraces (Tipparat et al 2012). Nevertheless, this is the first time that such a wide range in chemotype II variability has been unequivocally assigned to genotype and heterozygosity of THCAS and CBDAS.…”
Section: Chemotype II Variabilitymentioning
confidence: 41%
See 3 more Smart Citations
“…4). GC analysis of chemotype II has typically demonstrated a more narrow range skewed towards a high CBD total to THC total ratio (De Meijer et al 1992;Hillig and Mahlberg 2004;Weiblen et al 2015), although a low CBD total to THC total ratio similar to those reported here have been observed in Southeast Asian landraces (Tipparat et al 2012). Nevertheless, this is the first time that such a wide range in chemotype II variability has been unequivocally assigned to genotype and heterozygosity of THCAS and CBDAS.…”
Section: Chemotype II Variabilitymentioning
confidence: 41%
“…However, this is unlikely to be the case, as the distributions of chemotypes I, II, and III appear to be sufficient to account for the variation observed within the gene pool (Fig. 3) (De Meijer et al 2003;Hillig and Mahlberg 2004;Pacifico et al 2006).…”
Section: Chemotype II Variabilitymentioning
confidence: 96%
See 2 more Smart Citations
“…Based on proportions of CBD and THC levels, they suggested that there are two species, C. sativa and C. indica, that contain six subspecies 1 . Hillig later published a broader study identifying three species -adding C. ruderalis to the mix 2 .…”
Section: Molecular and Genetic Techniquesmentioning
confidence: 99%